Novo código florestal brasileiro e as cotas de reserva ambiental sob a ótica da pequena propriedade rural: um estudo de caso - Pereira, Angela Ceni Davoglio (2017)
The Federal Law n. 12.651 / 2012 refers to the native vegetation protection named by the specialized doctrine as New Brazilian Forest Code. Among the main changes in it, there is a new compensation mechanism of Legal Reserve Area called Environmental Reserve Quotas. The new legislation allows the rural landowner to transform the surplus area of his Legal Reserve into Environmental Reserve Quotas corresponding to each hectare of native vegetation. However, small rural property, that is, the one which has up to four (4) fiscal modules, can institute the Environmental Reserve Quotas over the entire size of its legal reserve area, not only over the surplus area. In addition, the small property is free to maintain the minimum percentage of legal reserve area, since the area had been consolidated on July 22, 2008, and new deforestation is prohibited. Because of the many peculiarities and the complexity of issues involving the environment and sustainable development, to the present piece of research a case study was chosen in the Community of the Damaceno Line, a rural area in the municipality of PatoBranco, located in the Atlantic Forest Biome, of plant formation Mixed Ombrophylous Forest Montana. The community is inserted in the macro-area of agricultural stock, bathed by the Pato Branco River and its tributaries (Rio Pinheiro, Rio da Divisa), and from where SANEPAR collects the water to supply the municipality. To understand how this community perceives environmental issues, a semi-structured research was used, containing a form and an interview, as well as methods such as the dialogical analysis of discourse and environmental perception. The obtained results made a correlation between the sustainable development, the payment of environmental services and compensation of the legal reserve area for quotas of environmental reserve, by means of interdisciplinary orientation. In addition, due to the methods used, a historical rescue was made regarding on the emergence of legal reserve area compensation in the Brazilian legal system, and on the formation of the Linha Damaceno Community, which has also demonstrated great historical wealth for the municipality of PatoBranco. In relation to the main theme of the research, the possibility of commercialization of Environmental Reserve Quotas by the small landowners of the Damaceno Line, it was concluded that there are properties that match all requirements currently formulated by the New Forest Code, however few farmers have shown interest on it, mainly due to the limitations that the property would have after the institution of the Environmental Reserve Quotas. Another important factor was the environmental perception regarding the farmers’ favoring who deforested their legal reserve areas and today can use the compensation mechanism without the need to restore the minimum percentages of the Legal Reserve Area.